Facilitation of Balsam Fir by Trembling Aspen in the Boreal Forest: Do Ectomycorrhizal Communities Matter? - Nagati, Mélissande; Roy, Mélanie; Desrochers, Annie; Manzi, Sophie; Bergeron, Yves; Gardes, Monique (Frontiers in Plant Science, 2019)
Succession is generally well described above-ground in the boreal forest, and several studies have demonstrated the role of interspecific facilitation in tree species establishment. However, the role of mycorrhizal communities for tree establishment and interspecific facilitation, has been little explored. At the ecotone between the mixed boreal forest, dominated by balsam fir and hardwood species, and the boreal forest, dominated by black spruce, several stands of trembling aspen can be found, surrounded by black spruce forest. Regeneration of balsam fir seems to have increased in the recent decades within the boreal forest, and it seems better adapted to grow in trembling aspen stands than in black spruce stands, even when located in similar abiotic conditions. As black spruce stands are also covered by ericaceous shrubs, we investigated if differences in soil fungal communities and ericaceous shrubs abundance could explain the differences observed in balsam fir growth and nutrition. We conducted a study centered on individual saplings to link growth and foliar nutrient concentrations to local vegetation cover, mycorrhization rate, and mycorrhizal communities associated with balsam fir roots. We found that foliar nutrient concentrations and ramification indices (colonization by mycorrhiza per length of root) were greater in trembling aspen stands and were positively correlated to apical and lateral growth of balsam fir saplings. In black spruce stands, the presence of ericaceous shrubs near balsam fir saplings affected ectomycorrhizal communities associated with tree roots which in turn negatively correlated with N foliar concentrations. Our results reveal that fungal communities observed under aspen are drivers of balsam fir early growth and nutrition in boreal forest stands and may facilitate ecotone migration in a context of climate change.